The influence of generational differences on the Malaysian housing preferences / Hafiszah Ismail - Ismail, Hafiszah (2016)
Literatures and models on property development evidences demographics as the long term trends especially the populations as one of the main factors that influence the property development process. Changes of demographics would influence the economic in general and the property market in specific besides the public policy implications that may also affects the behaviour of many actors of the property development sector. People live in households and households need housing and thus various demographic changing trends would contribute to dramatic change that affects the society and the generations. Changing demographic trends would give effects on the property market especially on the housing demand thus this give reason why more studies especially on the relationship between population and housing is greatly needed. Previous studies on demographic changes and housing demand show that focus were given mainly to the senior (elderly) generation namely the 'Baby Boom/Baby Boomers' Generation especially on the impacts toward the housing prices. As the numbers of this senior (elderly) population and their mean age currently continues to increase and projected to continually arise annually alongside with the other populations due to improvement of the health quality and lifestyle thus studies on current and future senior (elderly) housing preferences were relevant to guarantee better housing provisions of this specific population. In relevance, differences between generations have a large influence on our society, with younger generations continually being accompanied by new and different attitudes and values' (Roberts et. al., 2000). Therefore, there is also an imperative need to include different categories of generation namely Generation X (Gen-X), Generation Y (Gen-Y) and Generation Z (Gen-Z) in the discussions of housing particularly on the preferences. Despite on the importance, intense debate on how demographics drive the demand for housing reveals that empirical evidence is still not conclusive, especially in an international context. This is stressed by Mulder (2006) that, 'given the fundamental demographic change currently underway, it is surprising how few studies have researched the effect of demographics on housing market for Europe and Asia'. The aim of this study is to provide and in-depth overview on the influence of generational differences towards the Malaysian housing consumers' preferences. The main objective of this study is show that demographic/population changes do influence the housing preferences especially on the generations. This study employs mixed methods approaches. Seven (7) of the local authorities from the City Councils, Municipalities and District Councils along with two (2) housing developers in Selangor were interviewed for this study. The main purpose of the conducted interviews (semi-structured interview) is to determine the considerations and level of extend given on the demographic (population) changes in the planning for housing currently practised by these main actors. A total numbers of 678 housing consumers from different generations in Selangor, Malaysia were managed to be surveyed (questionnaires survey) to ascertain the current, future and senior (elderly) housing environment preferences. The questionnaires responses were analysed by using the SPSS, the Paired Comparisons/Pair-wise and the Analytic Hierarchy Process (ARP) methods of analysis. The main findings reveal that Safety, Health and Convenience were listed as the first three (3) important factors of the Residential Environment Preferences by the Malaysian generations, followed by the other two (2) factors namely Community and Amenity. As for the senior (elderly) housing, the findings reveal the acceptance of the generations with the introduction of the Age-Restricted Community Concept. Thus, this study will provide comprehensive findings on the housing preferences of the generations covering the current, future and elderly (senior) housing preferences. Detail findings derived from this study of housing, population and generations will provide beneficial information to various parties of the property development especially the policy makers and the involving main actors. Detail understanding on the matter would provide information that can be use as guidance to able and assist these concerning parties of property development for better planning and delivery of housing provisions that would benefit the current and future generations.